2021
DOI: 10.1213/ane.0000000000005575
|View full text |Cite
|
Sign up to set email alerts
|

Driving Pressure–Guided Individualized Positive End-Expiratory Pressure in Abdominal Surgery: A Randomized Controlled Trial

Abstract: BACKGROUND: The optimal positive end-expiratory pressure (PEEP) to prevent postoperative pulmonary complications (PPCs) remains unclear. Recent evidence showed that driving pressure was closely related to PPCs. In this study, we tested the hypothesis that an individualized PEEP guided by minimum driving pressure during abdominal surgery would reduce the incidence of PPCs. METHODS: This single-centered, randomized controlled trial included a total of 148… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“… 15 , 21 Recently, a single–centre randomised clinical trial showed that using driving pressure–guided individualized PEEP levels resulted in less clinically significant postoperative pulmonary complications compared to using a fixed PEEP in patients undergoing open upper abdominal surgery. 27 These findings should be verified in future randomised clinical trials. The absence of an association between driving pressure and the occurrence of postoperative pulmonary complications in our study could be due to a lack of statistical power.…”
Section: Discussionmentioning
confidence: 87%
“… 15 , 21 Recently, a single–centre randomised clinical trial showed that using driving pressure–guided individualized PEEP levels resulted in less clinically significant postoperative pulmonary complications compared to using a fixed PEEP in patients undergoing open upper abdominal surgery. 27 These findings should be verified in future randomised clinical trials. The absence of an association between driving pressure and the occurrence of postoperative pulmonary complications in our study could be due to a lack of statistical power.…”
Section: Discussionmentioning
confidence: 87%
“…Our findings suggest that driving pressure-oriented ventilation reduces the incidence of PPC S in patients undergoing thoracic surgery, which is consistent with previous findings ( 1 ). Despite some heterogeneity in the type of surgery, the results of previous studies have demonstrated that driving pressure-oriented ventilation can reduce the incidence of PPC S and improve patient prognosis ( 1 , 34 ). Since driving pressure is a new concept, this strategy is more widely used in patients with ARDS, and the number of RCTs that have focused on this aspect of thoracic surgery is limited.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting finding in the study by Zhang et al 2 was that mechanical power (MP) of ventilation was higher in the ΔP-guided PEEP group. MP can be seen as the amount of energy transferred from the ventilator to the lung, and has been proposed, alongside ΔP, as an additional biomarker to guide ventilation.…”
Section: To the Editormentioning
confidence: 93%
“…In their study, Zhang et al 2 used the first approach, ie, they used incremental PEEP trials. The “Driving PrESsure DurIng GeNeral AnesThesIa for Open AbdOmiNal Surgery” (DESIGNATION) study is an international multicenter ongoing randomized clinical trial in which a decremental PEEP trial is used to select the best PEEP, after an initial incremental PEEP trial to 20 cm H 2 O as a recruitment maneuver.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation